Determination of the Lift and Drag of 2D Planing Flat Plate Riding on the Free Surface - Rezaei, Amin; Ghassemi, Hassan; Noshadi, Esmail (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
The behavior of planing hull is very similar to planing flat plate. So to treat the planing hull performance at moderate Froude number, 2D planing flat plate was analyzed in different Froude number between 0.5 and 1. Finite volume, using ANSYS-CFX v14 software with RNG turbulence model was used to simulate planing plate. The numerical results of the pressure distribution, free surface profile, lift and drag at different AOAsare presented and discussed.Present calculations are compared with Kramer et al [7] results and show almost good agreement.